Microneedles at the Forefront of Next Generation Theranostics - Chan Wang; Yuan Yang; Jiaqi Zhang; Hanrui Zhang; Qian Wang; Shengmei Ma; Pengfei Zhao; Zhou Li; Yuxin Liu (Advanced Science, 2025)
Abstract Theranostics, combining therapeutic and diagnostic functions, marks a revolutionary advancement in modern medicine, with microneedle technology at its forefront. This review explores the substantial developments and multifaceted applications of microneedles, which have evolved from basic transdermal drug delivery devices to sophisticated diagnostic and therapeutic platforms. Microneedles enhance access to biomarkers via interstitial fluid, enabling real‐time monitoring of physiological conditions, such as glucose and hormone levels, thus facilitating continuous health tracking. The evolution of microneedle design from solid to dissolvable forms broadens their utility from mere drug delivery to complex sensing and therapeutic applications, including insulin delivery for diabetes management, vaccination, and gene therapy. This paper delves into the integration of microneedles with wearable technologies, highlighting their role in closed‐loop systems that combine real‐time monitoring with dynamic, precise therapeutic delivery. By addressing gaps in the literature regarding their integrated diagnostic and treatment capabilities, this review underscores the pivotal role of microneedles in personalizing medicine. It concludes with a visionary perspective on the future trajectory of microneedle technology, emphasizing its potential to revolutionize therapeutic strategies through enhanced efficacy, safety, and patient compliance.